Representing spatial relationships within smart cities using ontologies - Reed, Tristan; McMeekin, David; Reitsma, F. (Springer, 2017)
To be effective, smart cities require the relationships between physical phenomena such as the natural and built environment to be mapped and explored to enable better understanding of these phenomena. Using linked ontologies to represent these relationships supports multiple views on spatial data, allowing users to explore that data with concept browsing or spatial feature browsing in a way which is linked. The design for a prototype application is presented, demonstrating a process using modern web technologies that allows the user to explore linked data in an interlinked graph and map format simultaneously. This technique allows users to evaluate and interpret the semantic and spatial linkages between both elements of the built environment and the intangible properties of said elements. The prototype demonstrates the usefulness of an approach, achieved through semantic querying, with scope for future additions to allow different forms of exploration.